Imaging in glaucoma care pathways in the UK. (2nd April 2016) - Lee, Becky
Abstract: Glaucoma is an incurable disease of the eye that affects 2% of over 40s in the United Kingdom and 5% of those over 80. The National Institute for Health and Care Excellence (NICE) estimates that the disease affects around 480, 000 people in the United Kingdom, with over a million glaucoma-related hospital outpatient appointments each year. This paper aims to establish the care pathways for glaucoma across the United Kingdom and the perceived value of imaging. A questionnaire was distributed to members of the Ophthalmic Imaging Association to identify imaging protocols with glaucoma; results indicated that there was variation between hospitals. The perceived clinical value of imaging from staff involved in the pathway was also explored.